2005
DOI: 10.1152/ajpregu.00022.2005
|View full text |Cite
|
Sign up to set email alerts
|

Putative antihyperpyretic factor induced by LPS in spleen of guinea pigs

Abstract: We reported previously that the onset of LPS-induced fever, irrespective of its route of administration, is temporally correlated with the appearance of LPS in the liver and that splenectomy significantly increases both the febrile response to LPS and the uptake of LPS by Kupffer cells (KC). To further evaluate the role of the spleen in LPS fever production, we ligated the splenic vein and, 7 and 30 days later, monitored the core temperature changes over 6 h after intraperitoneal (ip) injection of LPS (2 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…Interestingly, large amounts of H-PGDS are present in the rat spleen (37), the organ in which the COX-1 pathway was activated at the onset of LPS hypothermia. Furthermore, Feleder et al (24,25) have recently shown that splenectomy or splenic vein ligation enhances LPS fever, and they have proposed that LPS causes the synthesis of a cryogenic lipid in the spleen. Our recent experiments (E. Pakai, A. Garami, T. B. Nucci, A.…”
Section: Perspectives and Significancementioning
confidence: 99%
“…Interestingly, large amounts of H-PGDS are present in the rat spleen (37), the organ in which the COX-1 pathway was activated at the onset of LPS hypothermia. Furthermore, Feleder et al (24,25) have recently shown that splenectomy or splenic vein ligation enhances LPS fever, and they have proposed that LPS causes the synthesis of a cryogenic lipid in the spleen. Our recent experiments (E. Pakai, A. Garami, T. B. Nucci, A.…”
Section: Perspectives and Significancementioning
confidence: 99%
“…Using fluorescence-labeled endotoxin, he demonstrated that the onset of fever correlated with the appearance of endotoxin in liver Kupffer cells (19). In addition, he discovered that the interaction between endotoxin and liver Kupffer cells could be restrained by factors generated by the spleen (15) and that these splenic factors could reduce endotoxin uptake by liver Kupffer cells and the concomitant febrile responses induced by endotoxin (16). These results strongly substantiated the thesis that an interaction between bacterial endotoxin and liver Kupffer cells activates the complement system, which then produces C5a to induce fever.…”
Section: Induction Of Fever By Complement Activationmentioning
confidence: 99%
“…We also found that intraveneous injection of ultra‐filtered (molecular weight cutoff 10 kDa) splenic tissue extracts attenuates LPS‐induced fever, and the splenic inhibitory factor may exist in the protein‐free part of the spleen extract. These findings suggest that this factor is a lipid, perhaps a prostanoid (Feleder et al , ). Prostanoids are produced by the spleen, are released into the splenic vein, and thereby affect Kupffer cell activity.…”
Section: Introductionmentioning
confidence: 96%
“…). Previously, we proposed a novel, unrecognized, endogenous anti‐hyperpyretic mechanism that may limit exaggerated fevers (Feleder et al , , ). This hypothesis was based on data showing for the first time that the spleen may modulate the febrile response to lipopolysaccharide (LPS).…”
Section: Introductionmentioning
confidence: 99%